Search for a CP-odd Higgs boson decaying into a heavy CP-even Higgs boson and a Z boson in the ℓ+ℓ−t¯t and ν¯νb¯b final states using 140 fb−1 of data collected with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Journal of high energy physics, 2024)
A search for a heavy CP-odd Higgs boson, A, decaying into a Z boson and a heavy CP-even Higgs boson, H, is presented. It uses the full LHC Run 2 dataset of pp collisions at √s = 13 TeV collected with the ATLAS detector, corresponding to an integrated luminosity of 140 fb−1. The search for A → ZH is performed in the ℓ+ℓ−t¯t and ν ¯νb¯b final states and surpasses the reach of previous searches in different final states in the region with mH > 350 GeV and mA > 800 GeV. No significant deviation from the Standard Model expectation is found. Upper limits are placed on the production cross-section times the decay branching ratios. Limits with less model dependence are also presented as functions of the reconstructed m(t¯t) and m(b¯b) distributions in the ℓ+ℓ−t¯t and ν ¯νb¯b channels, respectively. In addition, the results are interpreted in the context of two-Higgs-doublet models.